2022
DOI: 10.3390/ani12162146
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Circulating Leukocytes Obtained during the Recovery from Clinical Mastitis Caused by Escherichia coli in Holstein Dairy Cows

Abstract: The risk and severity of clinical infection with Escherichia coli as a causative pathogen for bovine mastitis is influenced by the hosts’ phenotypic and genotypic variables. We used RNA-Seq analysis of circulating leukocytes to investigate global transcriptomic profiles and genetic variants from Holstein cows with naturally occurring cases of clinical mastitis, diagnosed using clinical symptoms and milk microbiology. Healthy lactation-matched cows served as controls (CONT, n = 6). Blood samples were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 72 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…The downregulation of some aspects of hepatic immune function in cows from their second lactation onwards suggests that their increase in milk production in early lactation compromises immune function due to the competition for nutrients. This, in turn, would predispose these older animals to mastitis and uterine disease [ 86 , 87 , 88 , 89 ], both major risk factors leading to culling [ 9 , 90 ]. On the other hand, antimicrobial peptides were expressed at a higher level in the older cows, possibly in response to such infections.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of some aspects of hepatic immune function in cows from their second lactation onwards suggests that their increase in milk production in early lactation compromises immune function due to the competition for nutrients. This, in turn, would predispose these older animals to mastitis and uterine disease [ 86 , 87 , 88 , 89 ], both major risk factors leading to culling [ 9 , 90 ]. On the other hand, antimicrobial peptides were expressed at a higher level in the older cows, possibly in response to such infections.…”
Section: Discussionmentioning
confidence: 99%
“…These can not only kill the invaded organisms directly but also assist by modulating other immune and antimicrobial processes [65][66][67]. Upregulation of antimicrobial peptides in the leukocyte transcriptomic profiles has previously been demonstrated in cows with clinical mastitis [47,68] and metritis/endometritis [69,70].…”
Section: Comparison Of the Effects Of The High And Low Concentrate Di...mentioning
confidence: 97%
“…NLRs are cytosolic pattern recognition receptors which are activated by various non-self-components including bacterial peptidoglycan, potentially initiating NF-kappa B-/AP-1-dependent expression of pro-inflammatory cytokines, expression of type I interferons, autophagy and inflammation [46]. Our recent study demonstrated that this pathway was upregulated in leukocytes from E. coli-infected cows [47]. Another gene identified was MPO, encoding myeloperoxidase, an enzyme stored in azurophilic granules of PMNs and macrophages.…”
Section: Comparison Of the Effects Of The High And Low Concentrate Di...mentioning
confidence: 99%
“…According to an estimate, 80 species of bacteria, including E. coli and Salmonella , could pose a severe threat to poultry production [ 29 ]. Mastitis, induced by Staphylococcus aureus , Streptococcus agalactiae , Corynebacterium bovis , Streptococcus uberis , Streptococcus dysgalactiae , E. coli , Serratia marcescens and Proteus mirabilis in dairy cows, has been an economic welfare problem for dairy farms [ 30 , 31 , 32 ]. To date, many studies have reported main antibiotic resistant bacteria from different animal-derived foods in some countries, including E. coli ( Table 1 ), Salmonella spp.…”
Section: Foodborne Pathogenic Bacteria and Antibiotic Resistancementioning
confidence: 99%
“…ARGs and their resistance to the AGPs of E. coli , Salmonella spp., Staphylococcus spp., and Listeria spp. are shown in Table 7 [ 31 , 35 , 38 , 60 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ]. According to the data, different species have their own ARGs.…”
Section: Antibiotic Resistance Genes and The Impact Of Eos And Their ...mentioning
confidence: 99%